2018
DOI: 10.1167/iovs.18-24891
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Microvascular and Neural Changes in Diabetes Mellitus: An OCT-Angiography Study

Abstract: PURPOSE. To evaluate peripapillary vessel density and morphology in patients with diabetes mellitus (DM) without clinical signs of diabetic retinopathy (DR) and with mild, nonproliferative DR and to correlate with peripapillary nerve fiber layer (NFL) thickness. METHODS. One hundred seventeen eyes (34 healthy controls, 54 patients with DM without DR [noDR group] and 24 patients with mild DR [DR group]) were prospectively evaluated. All subjects underwent peripapillary and macular optical coherence tomography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 55 publications
11
72
0
Order By: Relevance
“…Developments in analytic software programs have enabled us to better evaluate the vessel density of the disc area. Previous studies have suggested that peripapillary capillary density was reduced in DM patients without DR and may be a useful parameter in the detection of early-stage DR [20][21][22]. In the present study, it was determined that the mean vessel density values of the whole disc and peripapillary area were also reduced in patients with microalbuminuria compared to patients with normoalbuminuria and controls.…”
Section: Discussionmentioning
confidence: 49%
“…Developments in analytic software programs have enabled us to better evaluate the vessel density of the disc area. Previous studies have suggested that peripapillary capillary density was reduced in DM patients without DR and may be a useful parameter in the detection of early-stage DR [20][21][22]. In the present study, it was determined that the mean vessel density values of the whole disc and peripapillary area were also reduced in patients with microalbuminuria compared to patients with normoalbuminuria and controls.…”
Section: Discussionmentioning
confidence: 49%
“…Vujosevic et al [38] found a significant correlation between OCTA parameters such as perfusion density or VD and RNFL thickness in the peripapillary area. Mase et al [39] explained this correlation that radial peripapillary plexus is the most important structure in maintaining RNFL integrity.…”
Section: Discussionmentioning
confidence: 98%
“…However, the vast majority of studies have been performed in patients with type 2 DM, [7][8][9][10][11][12][13][14][15] and many of them do not distinguish between patients with type 1 DM and patients with type 2 DM. [16][17][18][19][20] The pathophysiology of both DM types is considerably different, and patients present well-differentiated clinical characteristics. Whereas type 1 DM is less frequent, commonly affects younger patients, and it is a lifelong standing disease, patients with type 2 DM are more prevalent, they tend to be older, and frequently present concomitant cardiovascular pathologies, such as blood hypertension, metabolic syndrome, or dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%